KORELASI KADAR SERUM INTERLEUKIN6 DENGAN GEJALA UMUM KEGANASAN PADA PASIEN TUMOR INTRAKRANIAL DI RSUPN CIPTOMANGUNKUSUMO - Sheila Agustini, Tiara Aninditha, Lyna Soertidewi Kiemas, Teguh Asaad Suhatno Ranakusuma, Andhika Ra (NEURONA, 2012)
INTRODUCTION PROINFLAMMATORY CYTOKINES INDUCE HYPOTHALAMICPITUITARY AXIS HPA AND ACUTE PHASE RESPONSE WITH INTERLEUKIN6 IL6 BEING THE MOST POTENT STIMULATOR BRAIN TUMOR PATIENTS OFTEN SHOW NONSPECIFIC SYMPTOMS OF MALIGNANCY THAT MAY BE RELATED TO SICKNESS BEHAVIOR INDUCED BY CYTOKINES